2015
DOI: 10.1186/s12864-015-1387-6
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of variable number of tandem repeat typing identified through whole genome sequencing of Mycobacterium avium subsp. paratuberculosis on a national and herd level

Abstract: BackgroundMycobacterium avium subsp. paratuberculosis (MAP), the causative bacterium of Johne’s disease in dairy cattle, is widespread in the Canadian dairy industry and has significant economic and animal welfare implications. An understanding of the population dynamics of MAP can be used to identify introduction events, improve control efforts and target transmission pathways, although this requires an adequate understanding of MAP diversity and distribution between herds and across the country. Whole genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
72
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 37 publications
9
72
0
1
Order By: Relevance
“…Techniques such as AFLP and RAPD employ PCR to detect smaller genomic DNA fragments but are less utilized for epidemiological studies due to difficulties in standardization and reproducibility and limited discriminative power. Other typing methods based on repetitive sequences, such as SSR and MIRU-VNTR, are popular due to their ease of use and rapidity but, again, are limited with respect to their ability to discriminate within the two major strain types, and the typing results may not reflect the evolutionary relationships between isolates (10,12,25,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Techniques such as AFLP and RAPD employ PCR to detect smaller genomic DNA fragments but are less utilized for epidemiological studies due to difficulties in standardization and reproducibility and limited discriminative power. Other typing methods based on repetitive sequences, such as SSR and MIRU-VNTR, are popular due to their ease of use and rapidity but, again, are limited with respect to their ability to discriminate within the two major strain types, and the typing results may not reflect the evolutionary relationships between isolates (10,12,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diversity among M. avium subspecies paratuberculosis strains has been investigated using molecular techniques, such as restriction fragment length polymorphism (RFLP) and IS900 analysis (IS900 RFLP) (3), pulsed-field gel electrophoresis (PFGE) (4), amplified fragment length polymorphism (AFLP) analysis (5), random amplified polymorphic DNA (RAPD) analysis (6), mycobacterial interspersed repetitive unit-variable number tandem repeat (MIRU-VNTR) analysis (7), and short-sequence repeat (SSR) analysis (8). However, these techniques have limited discriminatory power when applied to M. avium subspecies paratuberculosis; although this power can be increased by combining complementary genotyping techniques, it is often insufficient for accurately determining relationships among isolates or global epidemiological studies (9, 10).Whole-genome sequencing (WGS) provides the ultimate resolution of isolates, and, unlike the techniques listed above, it can provide a phylogenetic context to facilitate global epidemiology studies and affirm epidemiological connections (10,11,12). Although WGS is becoming cheaper, it is still too expensive to be used for routine genotyping of M. avium subspecies paratuberculosis isolates and requires robust data handling and analysis processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Those with intolerance and gastrointestinal diseases lactose (Fonseca and Bruschi, 2009). The agent can survive in milk after heat treatment (Dimareli-Malli, 2010;Carvalho et al, 2012) and there is a strong suspicion que MAP can be the agent zoonotic, although there is controversy (Ahlstrom et al, 2015). In addition, there are economic losses due to the Decreased production of meat and milk of animals contaminated (Stehman, 1996;Oliveira et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…It has also been shown that the early stages of Map infection can occur in asymptomatic hosts that continue to shed viable bacteria in their faeces, leading to subsequent infection of other susceptible individuals (Whitlock et al, 2000). Therefore, there has been a lot of recent interest in understanding the dissemination of Map using source tracking and epidemiological studies (Ahlstrom et al, 2015; Ahlstrom et al, 2016; Leão et al, 2016; Bryant et al, 2016). …”
Section: Introductionmentioning
confidence: 99%